Quantitative metabolic profiling of lipid mediators. Issue 8 (4th July 2013) - Balgoma, David; Checa, Antonio; Sar, Daniel García; Snowden, Stuart; Wheelock, Craig E.; Schneider, Claus
<x xml:space="preserve">Abstract</x> Lipids are heterogeneous biological molecules that possess multiple physiological roles including cell structure, homeostasis, and restoration of tissue functionality during and after inflammation. Lipid metabolism constitutes a network of pathways that are related at multiple biosynthetic hubs. Disregulation of lipid metabolism can lead to pathophysiological effects and multiple lipid mediators have been described to be involved in physiological processes, (e.g. inflammation). Accordingly, a thorough description of these pathways may shed light on putative relations in multiple complex diseases, including chronic obstructive pulmonary disease, asthma, Alzheimer's disease, multiple sclerosis, obesity, and cancer. Due to the structural complexity of lipids and the low abundance of many lipid mediators, mass spectrometry is the most commonly employed method for analysis. However, multiple challenges remain in the efforts to analyze every lipid subfamily. In this review, the biological role of sphingolipids, glycerolipids, oxylipins (e.g. eicosanoids), endocannabinoids, and N‐acylethanolamines in relation to health and disease and the state‐of‐the‐art analyses are summarized. The characterization and understanding of these pathways will increase our ability to examine for interrelations among lipid pathways and improve the knowledge of biological mechanisms in health and disease.